Associations between cacao (Theobroma cacao) and shade trees in Southern Bahia Brazil - Cabala R., P.; Santana, M.; Cadima Z., A . (CATIE, Turrialba (Costa Rica) | GTZ, Eschborn (Alemania), 2021)
18 páginas, 4 figuras, 7 tablas, 40 ref.